Characterization of volcanic structures associated to the silicic magmatism of the Paraná-Etendeka Province, in the Aparados da Serra region, southern Brazil - Benites, Susana (2020)
The Paraná-Etendeka Magmatic Province is associated with the distensive tectonics that caused the rupture of the Gondwana continent during the Lower Cretaceous and generated an intense volcanism that covers South America and the NW portion of Namibia in Africa. In Brazil, this volcanic sequence is named Serra Geral Group and predominantly consists of basalts and subordinated silicic rocks. The goal of this study is to characterize the geomorphological features observed in the Aparados da Serra region, southern Brazil, and to evaluate the relationship between these structures and the primary silicic volcanic structures. The geomorphological features were fi rst identifi ed using remote sensing and then correlated with fl ow structures observed in the fi eld, as well as petrographic and geochemical data. AMS data were used to determine magnetic patterns and the direction of magmatic fl ow of the rocks. Despite the low degree of anisotropy, clear patterns of lineation and foliation were identifi ed in the studied rocks. Our data shows that Units I and II correspond to silicic lava fl ows linked to effusive fi ssure eruptions, presenting a dome morphology caused by differential erosion. Unit III rocks may correspond to true volcanic domes, whereas the Unit IV corresponds to the effusive feeder structures.